Este caso me desorientó - Devoto, Pablo Raul; Yasuda, Marcos Ezequiel; Iglesias, Brenda; Minghinelli, Federico; Bourguet, Martín; Recalde , Rodolfo (Revista Argentina de Neurocirugía, 2021)
Devoto, Pablo Raul; Yasuda, Marcos Ezequiel; Iglesias, Brenda; Minghinelli, Federico; Bourguet, Martín; Recalde Rodolfo.Servicio de Neurocirugía, Hospital de Clínicas “Jose de San Martin”, Universidad de Buenos Aires.